Organizational Development in Indian Organizations - Issues and Challenges - Tripathi, Priyanka; Tripathi, Prashant (Prabandhan: Indian Journal of Management, 2009)
As change has become inevitable part of our life Indian organizations are no exception to these compulsions. Today, they face numerous challenges and complexities, operating, as they do, in a highly volatile political and economic environment. This paper, while beginning with the basic characteristics of OD, goes through existing literature to look at the evolutionary phase by documenting the experiences of OD intervention in Indian organization. It also analyses the various issues emerging as major learning from these interventions. Finally it also indicates the challenges faced by the OD practitioner in India and also recommends the future directions for pursuing systematic research in OD areas in Indian context and to make it a relevant and pragmatic tool to bring about sustainable and long-term change.